The effect of fluoride toothpaste on root dentine demineralization progression: a pilot study - Juliana Nunes Botelho; Altair Antoninha Del Bel Cury; Wander José da Silva; Livia Maria Andaló Tenuta; Jaime Aparecido Cury (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The anticaries effect of fluoride (F) toothpaste containing 1100 µg F/g in reducing enamel demineralization is well established, but its effect on dentine has not been extensively studied. Furthermore, it has been shown that toothpaste containing a high F concentration is necessary to remineralize root dentine lesions, suggesting that a 1100 µg F/g concentration might not be high enough to reduce root dentine demineralization, particularly when dentine is subjected to a high cariogenic challenge. Thus, the aim of this pilot study was to evaluate in situ the effect of F toothpaste, at a concentration of 1100 µg F/g, on dentine demineralization. In a crossover and double-blind study, conducted in two phases of 14 days, six volunteers wore a palatal appliance containing four slabs of bovine root dentine whose surface hardness (SH) was previously determined and to which a 10% sucrose solution was applied extra-orally 8×/day. Volunteers used a non-F toothpaste (negative control) or F toothpaste (1100 µg F/g, NaF/SiO2) three times a day. On the 10th and 14th days of each phase, two slabs were collected and SH was determined again. Dentine demineralization was assessed as percentage of SH loss (%SHL). The effect of toothpaste was significant, showing lower %SHL for the F toothpaste group (42.0 ± 9.7) compared to the non-F group (62.0 ± 6.4; p < 0.0001), but the effect of time was not significant (p > 0.05). This pilot study suggests that F toothpaste at 1100 µg F/g is able to decrease dentine caries even under a high cariogenic challenge of biofilm accumulation and sugar exposure.